The relationship between early initiation of breastfeeding, exclusive breastfeeding with stunting and wasting in toddlers in Bolaang regency of east Mongondow - Punuh, Maureen I.; Akili, Rahayu H.; Tucunan, Adriansa (International Journal Of Community Medicine And Public Health, 2021)
Background: The forms of malnutrition in toddlers include stunting and wasting. Stunting and wasting that occurs in the first 1,000 days of life is at risk for stunted physical and cognitive growth and toddlers are susceptible to disease. One of the factors causing stunting and wasting is exclusive breastfeeding, which is preceded by successful initiation of early breastfeeding. The purpose of this study was to find out the relationship between early initiation of breastfeeding, exclusive breastfeeding with stunting and wasting in toddlers. Methods: This study was a quantitative research with an analytical survey method using a cross sectional design and it was undertaken in the working area of Tutuyan Health Center and Nuangan Health Center, Bolaang Mongondow Timur Regency. Samples were taken as many as 147 respondents using purposive sampling data collection techniques and met the inclusion and exclusion criteria. The data were analysed by univariate and bivariate using chi square statistical test. Results: The percentage of children under five with stunting was 27.9%, not stunting was 72.1%. Toddlers who experienced wasting by 22.4% and normal by 77.6%. Toddlers who received early initiation of breastfeeding were 42.9% while those who did not gain early initiation of breastfeeding were 57.1%. Toddlers who gained exclusive breastfeeding were 66.7% and those who were not exclusively breastfed were 33.3%. Conclusions: There was a relationship between early initiation of breastfeeding (p=0.000), exclusive breastfeeding (p=0.013) and stunting. There was a relationship between early initiation of breastfeeding (p=0.001), exclusive breastfeeding (p=0.001) and wasting in children under five in Bolaang Regency of East Mongondow. It is necessary to optimize stunting and wasting prevention programs and also cross-sectoral handling for stunting and wasting prevention in toddlers.